2018
DOI: 10.1016/j.surfcoat.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Uniform surface modification of polyethylene terephthalate (PET) by atmospheric pressure plasma jet with a horn-like nozzle

Abstract: This work reports on surface modification of polyethylene terephthalate (PET) polymer by an atmospheric pressure plasma jet (APPJ) operated with argon. A distinguishable feature of this device is that it terminates with a conical horn-like nozzle. Three different nozzles diameters were employed with the purpose to obtain uniform surface modification over large area. Treatments in small 3D objects that fit inside the conical horn were also conducted. In this study, water contact angle (WCA) measurements and X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…However, it has been reported that the simultaneous operation of many plasma jets can be challenging due to the strong electric repulsion between the neighboring plasma plumes resulting in plasma plume misalignment and, consequently, a non-uniform treatment [21]. Another alternative was reported by Mui et al [22], where a plasma jet terminating with a horn-shaped nozzle was used for the treatment of PET samples. The 60-mm-diameter conical nozzle allowed a homogeneous treatment over the entire PET sample that lies inside the horn.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the simultaneous operation of many plasma jets can be challenging due to the strong electric repulsion between the neighboring plasma plumes resulting in plasma plume misalignment and, consequently, a non-uniform treatment [21]. Another alternative was reported by Mui et al [22], where a plasma jet terminating with a horn-shaped nozzle was used for the treatment of PET samples. The 60-mm-diameter conical nozzle allowed a homogeneous treatment over the entire PET sample that lies inside the horn.…”
Section: Introductionmentioning
confidence: 99%
“…At first, the contact angles on the control sample for water and glycerol were 94.5 °and 84 °, but after plasma jet treatment, the contact angles were reduced to 57 °and 65 °, respectively, and became constant after a treatment time of 30 seconds. The reduction in contact angle might be due to the increase in roughness on the surface of PP [14,19,29,30]. 5 International Journal of Polymer Science Figure 6 shows the variation of surface energy and its polar and dispersive components of PP samples with a treatment time of 120 seconds.…”
Section: The Boltzmann Plot Methodmentioning
confidence: 99%
“…Initially, the contact angle of the untreated PET for water and glycerol was 82°and 88°, but after plasma treatment, the contact angle was effectively reduced to 26°and 30°, respectively, and became almost constant after the treatment time 50 seconds as shown in Figure 5. The reduction in the contact angle might be due to the change in the surface roughness as seen from SEM and AFM micrographs [23].…”
Section: Surfacementioning
confidence: 99%